Immune Checkpoint Inhibitor-Induced Myasthenia Gravis - Huang, Yi-Te; Chen, Ya-Ping; Lin, Wen-Chih; Su, Wu-Chou; Sun, Yuan-Ting (Frontiers in Neurology, 2020)
The development of immune checkpoint inhibitors (ICIs) has been a major breakthrough in cancer immunotherapy. The increasing use of ICIs has led to the discovery of a broad spectrum of immune-related adverse events (irAEs). Immune-related myasthenia gravis (irMG) is a rare but life-threatening irAE. In this review, clinical presentations of irMG are described and the risk of irMG-related mortality is examined using information from relevant studies. In 47 reported cases of irMG with clear causes of mortality, irMG appeared to be a distinct category of neuromuscular disorders and differed from classical MG in terms of its demographic patient characteristics, pathogenesis, serology profile, response to treatment, associated complications, and prognosis. Because of the high mortality of irMG, measures to increase the vigilance of medical teams are necessary to ensure timely identification of the signs of irMG and early treatment, particularly in the early course of ICI therapy. Diagnostic plans should be comprehensive and include the evaluation of other organ systems, such as the dermatological, gastrointestinal, respiratory, neuromuscular, and cardiovascular systems, in addition to the traditional diagnostic tests for MG. Treatment plans should be individualized on the basis of the extent of organ involvement and clinical severity. Additional therapeutic studies on irMG in the future are required to minimize irAE-related mortality and increase the safety of patients with cancer in the ICI era.